Peningkatan Pemahaman Mahasiswa dalam Perkuliahan Diagnostik Kesulitan Belajar Melalui Pengajaran Tutorial - Yulidar Ibrahim (Jurnal Konseling dan Pendidikan, 2017)
Each of students appealingly is entitled to gain a chance to achieve a satisfactory academic performance. In other words, s/he has the same opportunity to gain satisfactory learning outcomes. As the matter of fact, every student has various differences both in terms of intellectual abilities, talents, interests, willingness, attention, participation, family background, attitudes, and study habits that sometimes very conspicuous between one to another. Consequently, they receive diversity in satisfactory learning outcomes. This study aims to illustrate the improvement of students' understanding in diagnostic lectures of learning difficulties through tutorial teaching using method of Classroom Action Research (PTK). The subjects of the study were students enrolled in one of the difficulty diagnostic lecture sessions during semester of January - June 2016 amounted to 37 people. This research used observation format as research instrument through tutorial activity, diagnostic PTK diagnostic instrument and answer sheet. Data was analysed applying descriptive statistical techniques, whereas the analysis of diagnostic PTK instruments of learning difficulties based on scores obtained by the students and described in tabulation. The results of this study revealed that there is an improvement in student understanding in diagnostic lecture of learning difficulties through tutorial teaching.